2022
DOI: 10.1525/elementa.2022.00092
|View full text |Cite
|
Sign up to set email alerts
|

The complex Andes region needs improved efforts to face climate extremes

Abstract: The steep slopes, highlands, and valleys of the Andes mountain chain are inhabited throughout its formidable length. This unique characteristic does not repeat in any other mountain region. The Andes shape weather and climate in South America. However, proper understanding of atmospheric phenomena influenced by a daunting altitudinal gradient is still behind what is needed to produce detailed and consistent climate projections. Despite significant advances, global models misrepresent key precipitation and circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Nonetheless, there remains a pressing need for long-term and comprehensive precipitation monitoring on the eastern slopes of the Andean cordillera. The complex interactions between terrain and regional atmospheric circulation in this area give rise to a wide range of hydroclimatic regimes (Cazorla et al, 2022;Condom et al, 2020). For example, Newell et al (2022) demonstrated the importance of a network of rain gauges to capture the fine-scale spatiotemporal variability of rainfall in montane cloud forests in the northeastern Andes of Peru.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, there remains a pressing need for long-term and comprehensive precipitation monitoring on the eastern slopes of the Andean cordillera. The complex interactions between terrain and regional atmospheric circulation in this area give rise to a wide range of hydroclimatic regimes (Cazorla et al, 2022;Condom et al, 2020). For example, Newell et al (2022) demonstrated the importance of a network of rain gauges to capture the fine-scale spatiotemporal variability of rainfall in montane cloud forests in the northeastern Andes of Peru.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there remains a pressing need for long‐term and comprehensive precipitation monitoring on the eastern slopes of the Andean cordillera. The complex interactions between terrain and regional atmospheric circulation in this area give rise to a wide range of hydroclimatic regimes (Cazorla et al., 2022; Condom et al., 2020). For example, Newell et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the current distribution of aerosols and precipitable water vapor (PW) over climate vulnerable regions such as the tropical Andes is critical given that atmospheric composition continues to change rapidly and globally. The tropical Andes mountains are densely populated, unlike other mountain regions in the world, a remarkable feature in addition to their high altitude and continental scale length 1 . Examples of large and medium-size Andean cities are Medellín, Bogotá, Cali, Quito, Cuenca, Huancayo, and La Paz, but numerous towns of varied sizes are distributed all along Andean valleys and highlands (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, a more extensive coordinated investigation on the characteristics and origin of atmospheric aerosols and how they become distributed along the tropical Andes has been lacking. A dedicated look at PW in connection to rainfall is also necessary given that climate projections indicate that extreme precipitation events are expected to increase in the northwestern South American region, while more southern Andean latitudes are expected to suffer increased droughts 1 , 4 . Here, we present a consolidated study that delves into the status and changes in near surface and columnar aerosols and water vapor over the tropical Andes, which is relevant at a time of imminent climate change.…”
Section: Introductionmentioning
confidence: 99%